Ductile iron die castings

By controlling the oxygen and nitrogen content during the melting process and slowly cooling, combined with spheroidizer and mold temperature control, the problems of insufficient cold separation and graphite particles during the casting process are solved, and spherical graphite castings with high strength and high toughness are achieved.

JP7626371B2Active Publication Date: 2025-02-04TOHOKU UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021109463
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-07-15
Filing Date
2021-06-30
Publication Date
2025-02-04
Estimated Expiration
2036-07-15

AI Technical Summary

Technical Problem

The prior art is prone to cold separation during the gold casting process, and the number and particle size of spherical graphite cast iron are insufficient, resulting in poor mechanical characteristics, especially insufficient strength and toughness.

Method used

By controlling the oxygen and nitrogen content during the melting process, combined with the use of spheroidizer, slow cooling and precise mold temperature control are used to achieve the casting of spherical graphite cast iron without cold separation, with the number of graphite particles reaching 3000/mm² and the particle size is small and uniform.

Benefits of technology

A spherical graphite cast iron casting without cold partition is achieved, which significantly improves mechanical properties, especially strength and toughness, close to the level of cast steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626371000001
    Figure 0007626371000001
  • Figure 0007626371000002
    Figure 0007626371000002
  • Figure 0007626371000003
    Figure 0007626371000003
Patent Text Reader

Abstract

To provide a die cast product for ultrafine spheroidal graphite cast iron having ultrafine spheroidal graphite, in which the number of spheroidal graphite obtained by ultrafine refinement without chill in an as-cast state without annealing is more than that in the conventional ones and improvement in tensile strength, elongation and other characteristics is expected.SOLUTION: Provided is a mold casting of ultrafine spheroidal graphite cast iron containing no chill and having a structure of 500 pieces / mm2 or more of spheroidal graphite in an as-cast state, provided that cast iron containing Bi and cast iron with M exceeding 2.0 cm are excluded. Here, M=V / S where V is the product volume (cm3), and S is the product surface area (cm2).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal mold casting of ultrafine spheroidal graphite cast iron, more specifically, to a metal mold casting of ultrafine spheroidal graphite cast iron having ultrafine spheroidal graphite that is free of chill and has a greater number of ultrafine spheroidal graphite particles than conventional ones in an as-cast state without heat treatment, and that is expected to have improved tensile strength, elongation and other properties. [Background technology]

[0002] Spheroidal graphite cast iron is a type of pig iron casting (also known as cast iron) and is also known as ductile cast iron. In the case of gray cast iron, which is a type of cast iron, the graphite has a long, thin, highly anisotropic flake shape. In contrast, in the case of spheroidal graphite cast iron, the graphite has a spherical shape. Spheroidal graphite is achieved by adding a graphite spheroidizing agent containing magnesium, calcium, etc. to the molten metal just before casting.

[0003] Spheroidal graphite cast iron is made up of independent, globular graphite particles that lack strength, making the castings as tough and resilient as steel. Spheroidal graphite gives the material toughness, while spheroidized graphite gives the material strength and elongation. Currently, it is widely used as a material for industrial equipment, including the automotive industry.

[0004] The finer the graphite and the greater the number of particles, the greater the effect of suppressing the propagation of cracks during impact, and the greater the impact energy. In order to further improve the material, efforts are being made to make the spheroidized graphite finer and more uniformly dispersed. A typical metal structure of conventional spheroidal graphite cast iron is shown in Figure 3. As shown in Figure 3, conventional spheroidal graphite cast iron has a particle size of 400 particles / mm 2 Generally, it has nodular graphite. In addition, attempts have been made with respect to spheroidal graphite cast iron, as described in the patent and non-patent literature listed below.

[0005] In Patent Document 1 (JP Patent Publication 1-309939 A), the number of graphite grains is increased to 300 grains / mm by adding an appropriate amount of bismuth.2 This technology further adds an appropriate amount of nickel to achieve higher tensile strength and yield strength.

[0006] Patent Document 2 (JP Patent Publication 6-93369 A) provides a technology for free-cutting spheroidal graphite cast iron, which adds Ca to the molten metal in the presence of magnesium (Mg) and then adds Bi, thereby uniformly distributing finer spheroidal graphite than conventional spheroidal graphite cast iron and Ca compounds as a free-cutting element in the steel, thereby further improving the machinability and mechanical properties.

[0007] In Patent Document 3 (JP Patent Publication 2003-286538 A), the amount of Bi added to ductile cast iron is controlled to refine the graphite and improve the mechanical properties. In this technology, the synergistic effect of Bi and Ca results in a tensile strength of 450 MPa or more, an elongation of 20% or more, and a spheroidal graphite density of at least 2,000 particles / mm 2 The above measurements were made, and the spheroidization rate was maintained at 90% or more. Patent Document 4 (JP Patent Publication 2000-45011 A) discloses a method for casting spheroidal graphite cast iron containing 3.10 to 3.90% C, 2.5 to 4.00% Si, 0.45% or less Mn, 0.05% or less P, 0.008% or less S, 0.5% or less Cu, 0.3% or less Mo, 0.05% or less Mg, and 0.1% or less Bi+Sb+Ti, by a metal mold casting method so as to have an ultrafine graphite structure in the casting, and thereby the number of graphite grains is approximately 1900 grains / mm 2 The present invention provides a spheroidal graphite cast iron having an ultrafine graphite structure and preventing the occurrence of chill structure.

[0008] On the other hand, from the viewpoint of eliminating chill, Non-Patent Document 1 ("Cast Iron from the Viewpoint of Reaction Theory") shows the relationship between the nitrogen content in the molten metal and the chill depth, classifying nitrogen into hydrochloric acid soluble nitrogen and hydrochloric acid insoluble nitrogen, and showing the relationship between each of them and the chill depth (Non-Patent Document 1, pages 116-123). However, since this classification does not always apply, Non-Patent Document 2 classifies nitrogen into free nitrogen and other nitrogen, and attempts to reduce the chill length by controlling the amount of free nitrogen. Here, the amount of free nitrogen is the amount of nitrogen obtained by subtracting the amount of inclusion nitrogen from the total amount of nitrogen. Here, the amount of inclusion nitrogen is measured by JIS G 1228 (distillation-neutralization titration method).

[0009] In addition, Non-Patent Document 3 states that the number of chill-free spheroidal graphite particles is 850-1400 / mm 2 As-cast products such as the above are provided (Non-Patent Document 3, Table IX, first column above). [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 1-309939 [Patent Document 2] Japanese Patent Application Publication No. 6-93369 [Patent Document 3] JP 2003-286538 A [Patent Document 4] JP 2000-45011 A [Non-patent literature]

[0011] [Non-Patent Document 1] "Cast Iron from the Viewpoint of Reaction Theory" First Edition Published by the Japan Casting and Forging Association Published on March 31, 1992 [Non-Patent Document 2] "Effect of free nitrogen content on graphite solidification of cast iron" Japan Foundry Engineering Society, 163rd National Conference Abstracts (2013) 99 [Non-Patent Document 3] "Magnesium Map of the Spheroidalgraphite Structure in Ductile Castings" REVISTA DE METALURGIA, 49 (5) SEPTEMBRE-OCTUBRE 325-339 2013 Summary of the Invention [Problem to be solved by the invention]

[0012] In the conventional techniques described in the patent and non-patent documents mentioned above, die casting always involves the generation of chills. To eliminate chills, heat treatment is required. In addition, the number of spheroidal graphite particles in the structure of the spheroidal graphite cast iron produced by the above-mentioned production method is small, so that mechanical properties such as strength and elongation are not necessarily desired. Furthermore, in the technology of Patent Document 3, generation of white powder thought to be oxide was observed and elongation properties were lacking. In Non-Patent Document 2, the chill length is affected by the amount of free nitrogen, so the chill length is reduced by removing the free nitrogen. However, Non-Patent Document 2 states that chill occurs even though the casting is not a permanent mold casting, even though it contains a chill metal. In other words, it is suggested that if this technology is applied to a mold in which chill is more likely to occur than in a green mold, a chill with a longer chill length will occur. In addition, the number and particle size of spheroidal graphite in the structure are not mentioned. In the spheroidal graphite cast iron described in Patent Document 3, the number of spheroidal graphite particles is 2,000 particles / mm 2 However, this technology is not for metal mold castings. In other words, it is a metal mold casting with a spheroidal graphite particle count of 2,000 / mm 2 Nothing more is provided. In Patent Document 4, Bi and Sb are essential. In Non-Patent Document 3, among the die castings, the only product that is free of chill on either the surface or center is brake caliper G (7.5 kg, thickness 43 mm), and it is limited to products with a modulus M (cm) (M=V / S, V is volume, S is surface area) exceeding 2.

[0013] The present invention relates to a die casting method for spheroidal graphite cast iron that does not contain chill even in the as-cast state. Product The purpose is to provide. [Means for solving the problem]

[0014] The invention according to claim 1 is characterized in that the amount of nitrogen generated during melting is 0.9 ppm (by mass) or less, and in the as-cast state , the number of nodular graphite particles is 3000 / mm 2 That's all. This is a die-cast product made of ductile iron that does not contain chill. The invention according to claim 2 is the die-cast product of spheroidal graphite cast iron according to claim 1, in which M is 0.25 cm to 2.0 cm. M=V / S (V is the product volume (cm 3 ), S is the product surface area (cm 2 ) Effect of the Invention

[0015] According to the present invention, it is possible to perform die casting of spheroidal graphite cast iron that does not contain chill even in the as-cast state. Product can be provided. [Brief description of the drawings]

[0016] [Figure 1] 1 is a graph showing steps of an embodiment of the present invention. [Diagram 2] 1 is a structural diagram of a product manufactured according to an embodiment of the present invention. [Diagram 3] 1 is a graph showing the number of graphite nodules versus module of a product manufactured according to an embodiment of the present invention. [Figure 4] 1 is a graph showing mechanical properties of products manufactured according to an embodiment of the present invention. [Diagram 5] FIG. 2 is a metallographic structure diagram of conventional spheroidal graphite cast iron. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described with reference to FIG.

[0018] (melting process) In the melting process, the raw material for the spheroidal graphite cast iron is melted. As the raw material for the molten metal, for example, a raw material specified in JIS G5502 may be used. Other cast irons may also be used. In addition, other elements may be added as necessary. In addition, the composition range may be changed as appropriate. Examples of standards specified in JIS G5502 include FCD400-15, FCD450-10, FCD500-7, FCD600-3, FCD700-2, FCD800-2, FCD400-15, FCD450-10, FCD500-7, etc.

[0019] In addition to the above components, Bi, Ca, Ba, Cu, Ni, Cr, Mo, V, and RE (rare earth elements) may be appropriately added to the above-mentioned modifier molten metal raw materials or after melting the modifier molten metal raw materials. Furthermore, the CE (carbon equivalent) may be appropriately controlled to, for example, 3.9 to 4.6.

[0020] In the present invention, the temperature of the modifier molten metal is increased by further heating after melting. The increase in temperature removes oxygen from the modifier molten metal. The temperature is raised until it reaches the temperature T0, at which the removal of oxygen from within the original molten metal stops. When the temperature T0 is reached, the temperature is stopped and the temperature is maintained at T0 for a specified period of time. If the temperature is maintained, bubbles will be observed to form on the side of the crucible, at which point the temperature is stopped. The temperature is usually maintained for 2 to 10 minutes.

[0021] (Nitrogen removal process) The oxygen removal step is followed by nitrogen removal. In Non-Patent Document 2, free nitrogen is controlled. However, Non-Patent Document 2 is targeted at green sand molds and cannot be applied to dies as it is, and even if the free nitrogen control described in Non-Patent Document 2 is performed on a die, an increase in the number of spheroidal graphite particles is not necessarily observed. In the case of molds, it was found that the increase in the number of nodular graphite particles can be controlled by controlling the nitrogen based on the amount of nitrogen generated during melting. The amount of nitrogen generated during melting is the amount of nitrogen gas generated when a casting is melted. It is the amount of nitrogen generated when cast iron changes from solid to liquid. It can be checked with the final casting. Specifically, the measurement is performed according to the following procedure. To remove the oxide film, FUJI STAR500 (Sankyo Rikagaku) ​​sandpaper is used to remove the oxide film until the metallic luster on the surface disappears, and then the sample is cut into 0.5-1.0 g samples using a microcutter or rebar cutter. The sheared sample is washed with acetone to remove oil, and then dried in a dryer for a few seconds or vacuum dried before analysis. To begin the analysis, turn on the device, feed in helium gas, and perform a system check and leak check to confirm that there are no abnormalities. After stabilization, the analysis begins. Before the analysis, a discard analysis and blank measurement are performed, and a zero point correction is performed. For blank analysis, first set the crucible and add about 0.4g of a combustion improver (graphite powder). The combustion improver is added to improve the nitrogen extraction rate in the alloy. Outgassing is purged while flowing in He, and the inside of the sample chamber is replaced with He gas. Next, in order to remove the oxygen and nitrogen generated from the graphite crucible by preheating, the crucible is heated and held at a temperature equal to or higher than the analysis temperature (e.g. 2163°C) for 15 seconds, and the gas generated from the crucible is removed. After that, an analysis is performed under elevated temperature conditions, and the obtained value is used as the blank and corrected to be based on the zero point. Calibration curve creation: LECO 114-001-5 (nitrogen 8±2 ppm, oxygen 115±19 ppm), 502-873 (nitrogen 47±5 ppm, oxygen 34±5 ppm), 502-869 (nitrogen 414±8 ppm, oxygen 36±4 ppm), and 502-416 (nitrogen 782±14 ppm, oxygen 33±3 ppm) were used as standard samples and measurements were carried out three times each to create a calibration curve from the values ​​obtained. In temperature rise analysis, the material melts gradually from the lowest melting point, and at each temperature, the nitrogen contained in the molten material is extracted, resulting in a waveform peak. The amount of nitrogen per unit area is calculated from the total area of ​​the waveform peaks (sum of peak intensity values) and the amount of nitrogen obtained by analysis, and the nitrogen generated in the early stages of heating around 1250-1350°C is quantified. In the above analysis, the amount of nitrogen generated during melting can also be calculated by focusing on the nitrogen generated when cast iron changes from solid to liquid.

[0022] Nitrogen can be removed from the modifier molten metal by reducing its solubility in the modifier molten metal. To do this, the molten metal is cooled slowly. If the molten metal is cooled too quickly, the nitrogen may not be completely removed from the modifier molten metal. A cooling rate of 5°C / min or less is preferable. It is preferable to cool to T (℃) in formula 1. If cooling is performed to a temperature lower than T (℃), oxygen absorption will begin instead. In order to minimize both nitrogen and oxygen, it is preferable to cool to T (℃). From a practical standpoint, it is preferable to cool to (T-15℃) ±20 (℃). Formula (1) T=T k -273(℃) log([Si] / [C] 2 )=-27,486 / T k +15.47

[0023] In the process of slow cooling, nitrogen is released from the modifier molten metal. That is, the saturated solubility of nitrogen in the modifier molten metal decreases due to slow cooling, so that nitrogen that does not form a compound with other elements is released from the modifier molten metal. Note that, for example, bubbling of argon gas may be performed. Nitrogen escapes from the modifier molten metal due to such cooling.

[0024] (Spheroidization process) When the material is cooled to T (° C.) in Equation 1, spheroidization treatment is carried out. Here, the spheroidizing treatment is generally performed by adding Mg, but other methods (for example, spheroidizing treatment using a treatment agent containing Ce) may also be used. However, compared to Ce, Mg is overwhelmingly superior in the degree of refinement and the number of spheroidized carbon particles per unit. The Mg-containing treatment agent is preferably Fe-Si-Mg. In particular, it is preferable to use a treatment agent with a mass ratio of Fe:Si:Mg=50:50:(1-10). If the Mg ratio is less than 1, sufficient spheroidization cannot be achieved. If it exceeds 10, foaming occurs, causing gas entrapment. From this viewpoint, a ratio of 1-10 is preferable, and 1-5 is more preferable. It is preferable to carry out the spheroidizing treatment when the oxygen content is 20 ppm (by mass) or less. By keeping the oxygen content at 20 ppm or less, fine spheroidized graphite can be obtained.

[0025] (Inoculation process) Immediately after the spheroidizing treatment, inoculation is performed by adding, for example, Fe-Si to the molten metal. For example, Fe-75Si (mass ratio) is preferably used.

[0026] (Casting process) After adding the inoculant Fe-Si, casting is performed. It is preferable to perform casting without diffusing and stirring the inoculant. Taking into consideration factors related to equipment, it is preferable to shorten the casting time to, for example, 10 minutes or less, 5 minutes or less, 1 minute or less, or 5 seconds or less.

[0027] Casting is T p It is preferable to carry out the test within ±20°C. Here, T p =1350-60M(℃) M=V / S V is the product volume (cm 3 ), S is the product surface area (cm 2 )

[0028] The mold temperature is T d It is preferable to keep it within ±20(℃). T d =470-520M(℃) M=V / S V is the product volume (cm 3 ), S is the product surface area (cm 2 ) The mold temperature is preferably controlled according to the volume of the product. By controlling the mold temperature, the spheroidized graphite can be formed finer and more uniformly. However, depending on the conditions, poor molten metal flow may occur, so it is preferable to set the minimum mold temperature to 100°C.

[0029] (inoculation) The inoculation treatment is preferably carried out by adding Fe-Si. It is preferable to carry out this as soon as possible after the addition of Fe-Si. The shorter the time after inoculation, the finer the spheroidal graphite will be and the more spheroidal graphite will be per unit area. The shorter the time, the slower the diffusion of Fe-Si into the molten metal will be, and the higher the density of the spheroidal graphite will be. Although it depends on the apparatus, for example, it is preferable to carry out the casting within 10 minutes, more preferably within 5 minutes, and more preferably within 30 seconds, and even more preferably within 5 seconds. If casting is carried out in a state where Fe-Si is melted but not yet diffused, the number of spheroidized graphite particles increases dramatically compared to the case where it is uniformly melted. In order to further promote such a state, it is preferable to carry out casting without stirring. It is preferable to apply a heat insulating coat to the mold. In particular, a heat insulating coat is preferable, and a heat conductivity of 0.42 w / (m K) or less is particularly preferable. Specifically, it is preferable to apply a heat insulating coat to a thickness of 0.4 mm or more. EXAMPLES

[0030] Example 1 The raw material used had the following composition (mass%): C:3.66, Si:2.58, Mn:0.09, P:0.022, S:0.006, remaining Fe

[0031] When T in formula (1) for this raw material composition is calculated, it is as follows: T k =1698(K) T=T k -273=1425(℃)

[0032] The raw material was heated and melted in a furnace. After melting, the heating continued, passing 1425°C and continuing to increase in temperature. At temperatures above 1425°C, oxygen was removed. As the temperature increase continued, oxygen was found to be generated from the heat-resistant materials of the furnace when the temperature exceeded 1510°C. Therefore, the temperature increase was stopped at 1510°C and the temperature was kept at 1510°C for 5 minutes (referred to as "superheat" here). During this period, oxygen was removed from the modifier-free molten metal.

[0033] After keeping the temperature at 1510°C for 5 minutes, it was gradually cooled to 1425°C (=T°C) at an average rate of about 5°C / min. The temperature was lowered to 1440°C once, then increased to 1460°C, and then cooled at a rate of 5 min / min. That is, instead of cooling linearly to T°C after superheating, the melt was cooled faster than in a straight line, and then cooled linearly after the temperature was raised. By cooling slowly in this way, the amount of air components entrained in the molten metal could be greatly reduced compared to the case of cooling slowly in a straight line. This is thought to be because heating is required to cool linearly, and stirring during heating causes air entrainment. After superheating, it is preferable to perform natural cooling up to 1460°C so that air does not entrain. This reduces the amount of nitrogen mixed in from outside, and the amount of nitrogen, and therefore the amount of nitrogen generated during melting, can be more accurately controlled and reduced. As the temperature of the molten metal decreases, the solubility of nitrogen in the molten metal decreases, and nitrogen is generated. The amount of nitrogen saturated in the molten metal decreases with slow cooling, and unsaturated nitrogen is released from the molten metal. When the molten metal was cooled to temperature T, a portion was taken from the molten metal and the oxygen content was analyzed, which was less than 20 ppm.

[0034] Next, Mg treatment was carried out. Mg treatment was carried out by adding Fe-Si-3Mg. After Mg treatment, inoculation was carried out. For inoculation, an inoculant of 0.6 mass% Fe-75Si was used, and inoculation was carried out by stirring on the molten metal surface. The product was a coin with a diameter of 1 cm and a thickness (t) of 5.3 mm. The pouring temperature and mold temperature were set as follows. The mold was coated with 0.4 mm of heat insulating coating, which had a thermal conductivity of 0.42 w / (m K). Pouring temperature T p teeth, M=V / S=0.34 T p =1350-60M=1320℃ Mold temperature T d teeth, T d =470-520M=293.2(℃)

[0035] With the above-mentioned casting temperature and mold temperature settings, the mixture was poured into the mold 10 seconds after the end of inoculation. After pouring, the following results were obtained. The composition of the product was as follows (mass %): C:3.61, Si:3.11, Mn:0.10, P:0.024, S:0.008, Mg: 0.018.

[0036] The structure of the cast sample was observed by microscopic photography. The structure diagram is shown in Figure 2(a). Figure 2(b) is a reference example of a sand cast product. The spheroidal graphite was very fine and uniformly distributed. The number of spheroidal graphite particles was counted at 3222 particles / mm 2 It was.

[0037] Example 2 In this example, the amount of nitrogen generated during melting was changed, and the relationship between the amount of nitrogen generated during melting and the occurrence of chill was examined. was investigated. The experiment was carried out in the same manner as in Example 1. In each case, the mold surface was A thick insulating coat was formed. The results are shown below. Amount of nitrogen generated during melting T Pouring temperature Presence or absence of chill (ppm) (℃) 1.05 1415 1303 Yes 1.15 1439 1436 Yes 0.89 1430 1316 None 0.93 1429 1390 Yes 0.22 1432 1310 None 0.63 1432 1315 None 0.37 1430 1312 None As shown in the above results, the amount of nitrogen generated during melting is controlled to below 0.9 ppm, which is the critical value. In this case, no chill occurred. In addition, when there is no chill, the number of nodular graphite particles is much greater than when there is chill. There were many. (Comparative Example) In this example, after melting the raw materials, the temperature is raised to 1510℃, sand Casting was carried out into the mold. That is In this example, a sand mold was used. Other points were the same as in Example 1. The results are shown in Figure 2(b). In this example, 1005 pieces / mm 2 It was.

[0038] Example 3 In this example, an experiment was carried out using different coating forms. The following three types of coatings were used in the experiment. Other conditions were the same as in Example 1. A Heat insulating coating (thickness 0.4 mm) Thermal conductivity: 0.42 W (m K) B. Heat insulating coating (thickness 0.7 mm) Thermal conductivity: 0.2 W / (m K) C Heat insulating coating (thickness 0.2 mm) Thermal conductivity: 0.85 W / (m K) D Carbon black Thermal conductivity: 5.8W / (m K) A is the same as in Example 1. In the case of the heat insulating coating (AC), no chill was observed. However, in the case of the 0.2 mm thickness, the number of nodular graphite particles was smaller than that in the case of the 0.4 mm thickness, and the particle size was larger. In the case of the 0.7 mm thickness, the results were almost the same as in the case of the 0.4 mm thickness. In the case of carbon black, no chill was observed, but the number of nodular graphite particles was even less than in the case of the 0.2 mm thick heat insulating coating. Example 4 In this example, the mold temperature was changed within the range of 25°C to 300°C. The tests were conducted at five temperatures: 25°C, 178°C, 223°C, 286°C, and 300°C. The mold was coated with 0.4 mm of heat insulating mold coat. Other points were the same as in Example 1. Chilling was observed at 25°C. Chilling was not observed at other temperatures. The particle size was smallest at 286°C. Example 5 In this example, permanent mold castings were produced with the modulus (M) varied within the range of 0.25 to 2.0 (cm). The manufacturing conditions were the same as in Example 1. The number of nodular graphite particles was measured for each of the produced mold castings. The results are shown in FIG. 3 together with those for the green mold. Furthermore, no chill was observed in any of the products. As shown in Figure 3, the modulus (M) is at least 1500 pieces / mm 2 The structure contained fine spheroidal graphite as described above.

[0039] Example 6 In this example, a knuckle was prototyped and its mechanical properties were evaluated. In this example, a filter was installed at the sprue to remove as much foreign matter as possible, but a small amount of foreign matter still remained. The test results are shown in Figure 4 together with the conventional example. Evaluation of the mechanical properties of the knuckle prototypes showed that they exhibited the mechanical properties of cast steel, despite being made of spheroidal graphite cast iron. For example, the tensile strength of one of the knuckle prototypes was 525N / cm 2 The product has an elongation of 18.8%, while general spheroidal graphite cast iron has a tensile strength of 380N / cm 2 This resulted in 1.5 times the tensile strength, giving the material mechanical properties comparable to those of cast steel. [Industrial Applicability]

[0040] The present invention can also be applied to automobile parts such as knuckles and electrical / electronic device parts that require high toughness and strength.

Claims

1. A die-cast spheroidal graphite cast iron product which generates 0.9 ppm (mass) or less of nitrogen when melted, has 3,000 or more spheroidal graphite particles / mm 2 in an as-cast state, and contains no chill.

2. The spheroidal graphite cast iron according to claim 1, wherein M is 0.25 cm to 2.0 cm. M=V / S (V is the product volume (cm 3 ), S is the product surface area (cm 2 )

Citation Information

Patent Citations

  • Method for casting unchilled cast iron

    JP1988260667A

  • Spheroidal graphite cast iron and its manufacture

    JP1989309939A

  • Production of free cutting spheroidal graphite cast iron

    JP1994093369A

  • Spheroidal graphite cast iron and production of spheroidal graphite cast iron

    JP2000045011A

  • Tough, ductile cast iron and its manufacturing process

    JP2003286538A